The control dilemma in eating behavior: influence of temptation cues in restrained versus unrestrained eaters - Peláez-Fernández, María Angeles; Extremera, Natalio (Psicothema, 2011)
The present research explored the effects of pre-exposure to temptation primes and dieting primes on food intake, goal accessibility and explicit automatic evaluations of food-enjoyment and dieting goals among restrained and unrestrained eaters. Participants (n= 166) were randomly assigned to three conditions: food-cue, dieting, or control, in which they were exposed to incidental presentation of gourmet, fashion or geographic magazines, respectively. Words related to the goals of dieting and/or food- enjoyment were presented in a computer decision task following the incidental presentation of gourmet, dieting, and geographic magazine photographs. The computer task and the presentation of food were counterbalanced. Participants’ food intake was assessed in a taste-rating task. Restrained eaters ate more than did unrestrained eaters across the three conditions. Restrained eaters who were exposed to food cues ate more than did restrained eaters in the control condition and they evaluated the goal of dieting more negatively compared to restrained eaters in the other two conditions. These findings were inconsistent with ’Counteractive Self-Control Theory’ but consistent with previous studies on the effects of food-cue exposure in restrained eaters.